Space science - Harra, Louise K; Mason, Keith O (London, Imperial College Press, 2004)
This invaluable book provides an introduction to space science. It brings together the various space science disciplines in one volume, and will benefit a wide audience, particularly students starting their graduate studies. The text presents a unique outlook, which will encourage students to think in broad terms across the whole range of space science, from the Earth's climate system to cosmology. There are also chapters describing basic techniques necessary to progress in space science research.
Bibliography 459-467p.
Keywords: Astronomy; Space Science; Physics